(untitled) (Fiep Bulletin - online, 2011)
The study aimed to discuss and show content tenders concerning health related to human motion for high school physical education classes. This is a positive feature bibliographic job which its subject course has been from a systematic tender organized by Oliveira (2004b) that hint a field content sharing in four cores thereby body motion as the studied content field: "structure and building motion" , "playfull and sport expressive motion" , "expression and beat motion" and "motion and health". The last one was the work being tender focus which found support in literature checking that the tender core complying as law concerns so educator wishes that search for discipline legitimize. Lastly imply the subject and related have great importance to the field as for educational project legitimacy. Thus read that teacher should be able to work conceptually as the methodology in order to ensure the student capture and using.